SAY ON PAY: Regulation and Executive Compensation - Syrjälä, Olga (My University, 2019)
Due to the European Commission’s view that the financial crisis was largely caused by the passivity of shareholders and the short-term nature of their investment, Directive 2017/828 was implemented as a solution. With Say on Pay, shareholders are given the right to vote on executive compensation; increasing transparency between the company and its shareholders. As companies are becoming more international, it has been seen as a necessity to develop corporate governance to a direction where capital markets work together and allow cross-border investment. Describing different components of managements’ pay, companies need to come up with a clear and understandable remuneration policy, presented at the annual general meeting at least every four years. Compensation should be aligned to the long-term strategy and with the company’s strategic goals and key performance indicators and it should notably avoid guaranteed or discretionary compensation. The cornerstone for a productive shareholder engagement is upholding good corporate governance and active shareholder participation. High level of corporate governance may reduce managers’ earnings manipulation and tendency to commit fraud; in addition, it may also achieve a higher quality of information transparency. With Say on Pay, a potential step towards mitigating excessive CEO compensation might result when shareholders are given more power - opening also the discussion between management and shareholders.
Keywords: Corporate Governance; Say on Pay; Limited Liability Companies Act; Executive Compensation; fi=Talousoikeus|en=Business Law|; fi=Talousoikeuden maisteriohjelma|en=Master's Programme in Business Law|